2021
DOI: 10.1017/jfm.2021.891
|View full text |Cite
|
Sign up to set email alerts
|

On the role of turbulent large-scale streaks in generating sediment ridges

Abstract: The role of turbulent large-scale streaks or large-scale motions in forming subaqueous sediment ridges on an initially flat sediment bed is investigated with the aid of particle resolved direct numerical simulations of open channel flow at bulk Reynolds numbers up to 9500. The regular arrangement of quasi-streamwise ridges and troughs at a characteristic spanwise spacing between 1 and 1.5 times the mean fluid height is found to be a consequence of the spanwise organisation of turbulence in large-scale streamwi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 102 publications
(177 reference statements)
6
27
0
Order By: Relevance
“…Recent studies (e.g. Jie, Andersson & Zhao 2021;Scherer et al 2022) have also observed the contribution to particle clustering from not only buffer-layer structures but also large-scale ones. However, we do not fully understand the transport mechanism of particles with different relaxation times in high-Reynolds-number wall turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies (e.g. Jie, Andersson & Zhao 2021;Scherer et al 2022) have also observed the contribution to particle clustering from not only buffer-layer structures but also large-scale ones. However, we do not fully understand the transport mechanism of particles with different relaxation times in high-Reynolds-number wall turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…Scherer et al. 2021) but is outside the scope of the present work.
Figure 3.Instantaneous snapshots of the flow field and particle positions of case H6 at times ( a ) , ( b ) , ( c ) and ( d ) .
…”
Section: Evolution Of the Flow And Sediment Bedmentioning
confidence: 77%
“…( y, t) in case 1. There exists a ridge in the contours of C u L i ,τ L i2 ( y, t) with a negative slope, indicating that (Scherer et al 2022), the spatial-temporal correlation coefficients in figure 14 are larger than 0.8 for −2 < tu w /h < 2 and 0 < y/h < 0.5. This result is consistent with the observation in the works of Shrestha & Anderson (2020) and Deng et al (2020), that is, the intensities and spanwise locations of full-depth LCs are persistent for a period of 100 < tu w /h < 300.…”
Section: Scaling and Predictive Model Of Lcs Partmentioning
confidence: 98%
“…The above triple decomposition has been used to extract the CCs in turbulent Couette flows (Papavassiliou & Hanratty 1997) and full-depth LCs in shallow-water Langmuir turbulence (Tejada-Martínez & Grosch 2007;Deng et al 2019). Similar triple decomposition techniques were also used to study the coherent motions induced by streamwise-aligned roughness and riblets (Raupach & Shaw 1982;Choi, Moin & Kim 1993;Jimenez et al 2001;Garcia-Mayoral & Jimenez 2011;Jelly, Jung & Zaki 2014;Seo, Garcia-Mayoral & Mani 2015;Scherer et al 2022).…”
Section: Extraction Of Full-depth Lcsmentioning
confidence: 99%
See 1 more Smart Citation